Hypoxia in Korean Coastal Waters: A Case Study of the Natural Jinhae Bay and Artificial Shihwa Bay - Lee, Jiyoung; Park, Ki-Tae; Lim, Jae-Hyun; Yoon, Joo-Eun; Kim, Il-Nam (Frontiers in Marine Science, 2018)
Several coastal regions in Korea have suffered from hypoxia since the 1970s. We present the first review of Korean coastal hypoxia, focusing on its spatiotemporal variation, controlling factors, and effects on marine ecosystems. The review considers the two hotspots of the natural Jinhae Bay (JB) and artificial Shihwa Bay (SB), which are referred to as “Korean dead zones.” The hypoxia in the JB is attributed to eutrophication due to domestic and land-used waste input and thermal stratification based on the naturally sluggish water circulation, whereas the hypoxia in the SB is due to eutrophication resulting from domestic, land-used, and industrial waste input and haline stratification as a consequence of the artificially created water stagnation. The bottom-water hypoxia and stratification has resulted in excessive accumulation of phosphate in both bays, leading to an imbalance in nitrogen:phosphorus ratio between surface and bottom waters. Hypoxia has also created undesirable benthic community changes in the both bays: (1) mass mortality of large species and recolonization with elevated abundances of opportunists in JB, and (2) decrease of the number of species, abundance, and diversity of benthic communities in SB. Therefore, it behooves us to pay attention to these environmental changes. This review will be helpful in determining the direction of future studies of Korean coastal hypoxia.